THU0463-HPR Malnutration in rheumatology in acute care setting, riskfactors and interventions. (23rd January 2014) - Schärer Huber, P.; Villiger, P.; Wenger, C.; Hürlimann, B.
Abstract : Background: The prevalence of malnutrition in hospitalized patients in Switzerland is up to 40%. Only few studies about malnutrition have been conducted in rheumatology and often only with a small sample. Since 2010, the nutritional status of all hospitalized patients in the Clinic for Rheumatology at the University Hospital Berne, Inselspital has been assessed with the NRS 2002 adapted for the Clinic for Rheumatology as well as entry of quantities of every meal. Objectives: Questions: – What factors are influencing the risk for malnutrition in patients with a rheumatologic disease? – What interventions have a positive effect on the nutritional status of patients with a rheumatologic disease in an acute care setting? Methods: A literature research was made using the following key-words in different combinations: malnutrition, rheumatology, influencing factors, treatment and prevention, health promotion, risk factors, intervention. Additionally, the data of the NRS 2002 and the entry of quantities of the patients' meals from December 2010 to May 2011 were analysed using descriptive statistics. Results: The following influencing factors were found in the literature: Illness, age, motor restrictions (especially regarding the ability to eat self-dependently, means regarding the higher extremities), xerostomia, lesion of the oral mucosa, social isolation. These factors were integrated in the analysis of the clinical data. During data collection, at hospitalisation more than half of the patients were at risk for malnutrition or suffering from malnutrition. Additionally, with a longer hospital stay the nutritional status of the patients got worse. For the influencing factors, it can be assumed that rheumatic disease, motor restrictions and problems with the oral mucosa increase the risk for malnutrition. Looking closer at disease, a higher proportion of patients suffering from systemic sclerosis, rheumatoid arthritis or patients hospitalised for diagnostics have a risk for malnutrition. Concerning the entry of quantities of patients' meal it can be said that patients already ordering only a small meal usually do not eat the whole portion. It was also observed that the patients get more snacks in between meals when a dietician is involved. Conclusions: The main conclusion of this study is that malnutrition and the risk for malnutrition are important clinical problems in patients with a rheumatic disease. In clinical practice, the NRS-RIA proved to be easy to use to assess these patients. Thanks to the systematic entry of quantities, the daily dietary intake could be evaluated. Dieticians were integrated in time in patients' care, which had a positive effect on patients' dietary intake. As the average length of stay in the Clinic for Rheumatology is only ten days, it is important to think about the sustainability of these interventions. Patients in day care could be systematically assessed, to improve nutritional status also in non hospitalised patients. Especially for patients with systemic sclerosis, rheumatoid arthritis or patients hospitalised for diagnostics, a focused interprofessional care should be institutionalised, for instance by implementing standards or clinical pathways. Another possible preventive approach would be to improve rheumatologic patients' knowledge about "healthy nutrition". With the results of this small study, only tendencies can be shown which should be further evaluated. Disclosure of Interest: None Declared